THE EFFECT OF SUPERVISION AND DIVISION OF WORK ON EMPLOYEE WORK ETHICS AT PIA HOTEL PANDAN, CENTRAL TAPANULI REGENCY - Mutiara Sari; Nelly A. Sinaga; Rahmadiah Hanum (Cattleya Darmaya Fortuna, 2025)
The purpose of this study is to determine whether supervision and division of labor affect employee morale at Pia Hotel Pandan, Central Tapanuli Regency. This study is a descriptive quantitative approach using a saturated sample of 61 people. Data were analyzed using multiple linear regression analysis. The findings of the study indicate that supervision and division of labor can affect employee morale by 55.5%, while the remaining 44.5% can be influenced by other factors not discussed in this study. Supervision and division of labor together have a positive and significant effect on work enthusiasm, where F count (38.365) is greater than F table (3.16). Supervision has a significant effect on work enthusiasm, where the t-count value of 3.072 is greater than the t-table value of 2.001 (3.072 > 2.001) or significant (Sig-t) of 0.003 < α (0.05). Division of labor has the most dominant effect on work enthusiasm, where the t-count value of 5.045 is greater than the t-table value of 2.001 (5.045 > 2.001) or significant (Sig-t) of 0.008 < α (0.05). The multiple linear regression model obtained by the regression equation is Y = Y = 4.408 + 0.321X1 + 0.555X2 indicating a positive direction.